21.6k views
6 votes
Help !!!
See question in image.
Please show workings .


Help !!! See question in image. Please show workings . ​-example-1

1 Answer

8 votes

Answer:

see explanation

Explanation:

Given f(x) then the derivative f'(x) is

f'(x) = lim(h tends to 0 )
(f(x+h)-f(x))/(h)

= lim ( h to 0 )
(4(x+h)^2-2-(4x^2-2))/(h)

= lim ( h to 0 )
(4(x+h)^2-2-4x^2+2)/(h)

= lim( h to 0 )
(4x^2+8hx+4h^2-4x^2)/(h)

= lim( h to 0 )
(8hx+4h^2)/(h)

= lim ( h to 0 )
(4h(2x+h))/(h) ← cancel h on numerator/ denominator

= lim ( h to 0 ) 4(2x + h) ← let h go to zero

f'(x) = 8x

User Zec
by
6.1k points